X-ray powder data and bond valence of La0.65Sr0.35MnO3 after Rietveld refinement - Paiva-Santos, C. O. (2002)
Powder X-ray diffraction (XRD) data were collected for La0.65Sr0.35MnO3 prepared through an alternative method from a stoichiometric mixture of Mn2O3, La2O3, and SrO2, fired at 1300 degreesC for 16 h. XRD analysis using the Rietveld method was carried out and it was found that manganite has rhombohedral symmetry (space group R(3) over bar c). The lattice parameters are found to be a=5.5032 Angstrom and c=13.3674 Angstrom. The bond valence computation indicates that the initial inclusion of Sr occurs at higher temperature. (C) 2002 International Centre for Diffraction Data.